2015
DOI: 10.1108/ebr-03-2014-0024
|View full text |Cite
|
Sign up to set email alerts
|

Building the research culture in an African business school

Abstract: Purpose – This paper aims to report the efforts to reverse a dire research output trend at a Ghanaian Business School, following a similar effort at a business school in New Zealand in the 1990s. African universities are often challenged by resource constraints, ageing faculty and low compensation regimes. The consequences of these challenges are particularly felt in the area of the research output of faculty members in the business and management area. The problem of low research output has be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The findings reported in this paper add to the growing body of literature that tackles the problem of weak research productivity of African universities. While Puplampu (2015) proposes an intervention model, our research goes further to address the building of research cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The findings reported in this paper add to the growing body of literature that tackles the problem of weak research productivity of African universities. While Puplampu (2015) proposes an intervention model, our research goes further to address the building of research cultures.…”
Section: Discussionmentioning
confidence: 99%
“…Writers are beginning to argue that the conversation should shift to or urgently include questions about the human, psychological, behavioural, and intentional factors that make it possible to describe a university as research intensive or describe academics as research oriented. From an institutional as well as psychological standpoint, research by Pratt et al (1999) and more recently by Puplampu (2015) suggests that the behavioural and the intentional underscore the probability of academics carrying out research or engaging in knowledge producing activities. In other words, institutional facilitation and resource allocation per se may not achieve the research impetus that would lead to the sustained research through which knowledge may be created.…”
Section: Research Culture and Behavioural Intentionalitymentioning
confidence: 99%
“…It is also highly unlikely that African universities and business schools will cover related expenses, considering their own financial constraints (Darley & Luethge, 2016). Furthermore, poor research culture in African universities (Puplampu, 2015;Sawyerr, 2004) could render action research, as suggested by MM, very difficult to conduct.…”
Section: Community Service Learning: a Refined Approachmentioning
confidence: 99%